Entitlement theory of justice and end-state fairness in the allocation of goods - Biung-Ghi Ju; Juan D. Moreno-Ternero (University of Massachusetts, Department of Economics, 2016)
Robert Nozick allegedly introduced his liberal theory of private ownership as an objection to theories of end-state justice. Nevertheless, we show that, in a stylized framework for the allocation of goods in joint ventures, both approaches can be seen as complementary. More precisely, in such a context, self-ownership (the basis for Nozick's entitlement theory of justice) followed by voluntary transfer (Nozick's principle of just transfer) can lead to end-state fairness (as well as Pareto efficiency). Furthermore, under a certain solidarity condition, the only way to achieve end-state fairness, following Nozick's procedure, is to endorse an egalitarian rule for the initial assignment of rights.
Keywords: 330